Accepting risk in the acceleration of drug development for rare cancers. Issue 4 (April 2015) - Ashley, David; Thomas, David; Gore, Lia; Carter, Rob; Zalcberg, John R; Otmar, Renée; Savulescu, Julian
Summary Rare cancers collectively contribute a disproportionate fraction of the total burden of cancer. The oncology community is increasingly facing small numbers of patients with each cancer subtype, requiring cooperation and collaboration to complete multicentre trials that advance knowledge and patient care. At the same time, new insights into the biology of rare cancers have led to an explosion in knowledge and development of targeted agents. These insights and techniques are set to revolutionise the care of patients with cancer. However, drug development strategies and the availability of new agents for rare cancers are at risk of stalling owing to the ever-increasing complexity and costs of clinical trials. Finding solutions to these problems is imperative to the future of cancer care. We propose that a greater degree of risk sharing is needed than is currently accepted to enable the use of new methods with confidence, and to keep pace with scientific advancement.